Analysis of inter-core crosstalk in weakly-coupled multi-core fiber coherent systems - Pinheiro, B. R. P.; Rebola, J. L.; Cartaxo, A. V. T. (Journal of Lightwave Technology, 2021)
The influence of the inter-core crosstalk (ICXT) on the performance of weakly-coupled multi-core fiber (WC-MCF) systems with coherent detection and arbitrary inter-core skew is studied numerically and analytically. We analyze the evolution of the instantaneous ICXT power, induced by polarization division multiplexed quadrature amplitude modulation signals, short term average crosstalk (STAXT), and detected ICXT components along the time to get insight on how the ICXT affects the coherent system performance. Numerical results show that, with low skew-symbol rate product ($\ll$1), the STAXT can have large fluctuations along the time and the variance of the detected ICXT can also have large fluctuations along the time, causing large variations of the bit error rate (BER) along time. With large skew-symbol rate product ($\gg$1), the STAXT is almost constant along the time and, although the detected ICXT varies along time, the detected ICXT variance is almost constant along time leading to very small fluctuations of BER along time. Analytical expressions for the variance of the coherently detected ICXT, average BER and optical signal-to-noise ratio (OSNR) penalty are proposed and shown to agree with Monte-Carlo simulation results for arbitrary skew, modulation format order, and roll-off factor of the transmitted signals. Numerical results show that the maximum allowable ICXT level for 1 dB OSNR penalty increases when the skew augments and can reach 1.3 dB for a roll-off factor of 1. For most cases of interest of low roll-off factor, the increase of the maximum allowable ICXT level is very small. It is shown that the OSNR penalty estimates agree quite well with other authors' experimental results (with nearly zero roll-off factor).